Reflection of K.H. Ahmad Dahlan’s educational ideas for school development - Suripto, S. (Graduate School, Universitas Negeri Yogyakarta, 2017)
This research was aimed to reflect the form of K.H. Ahmad Dahlan’s educational ideas in schools. The kind of this reasearch was qualitative with multi sites approach. Reasearch was conducted at MTs Muhammadiyah 2 and Muhammadiyah 1 Vocational School – Trenggalek.The object of this research was the form of K.H. Ahmad Dahlan’s educational ideas whereas the subject was all the schools administrators. Data were collected through deep interview, documentation and observation techniques. Data validity was tested with; credibility, transferability, and confirmability. Data analysis model was interractionally each other; data reduction, data presentation, conclusion withdrawal, and verification. The research result were; first, at MTs Muhammadiyah 2, the form of K.H. Ahmad dahlan’s educational ideas covered: Muhammadiyah values, such as (a). TBC eradication, worry attitude towards the improvement of fundamentalist religious culture in the society (LDII), (b). Willingness to sacrifice attitude grown by the school founders’ core team, organizers, and administarators; (c). The spirit of dakwah and dedication for the nation and the religion. Second, at Muhammadiyah 1 Vocational School, it covered (a). Charity effort movement for all (rahmatan lilalamin); (b). Amar maruf nahy munkar was formed in the construction of all field of life, (c). Working was the spirit of movement organization.